TINJAUAN YURIDIS TERHADAP EKSISTENSI PENGATURAN MENGENAI LINGKUNGAN HIDUP DI DALAM UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 DAN KONSTITUSI REPUBLIK KELIMA PERANCIS - David Aprizon Putra (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2019)
Abstract: The loss of environmental interests in a battle that is clearly unbalanced is one proof that people, nations in this world still do not realize how very important and valuable it is to promote the existence of a living environment. The interests of the environment are the interests of life, not only human life but the life of all living things, the most important of course is that not only life today but life in the future. What will we inherit for the lives of our children and grandchildren later? Fighting that defeats the interests of the environment, not only occurs in the practical realm of the executive, but has also penetrated the legislative line which is certainly full of political content. A more in-depth study is needed regarding this matter; it is only natural that we see the clash between the environmental laws of one and the other environmental laws, not to mention the clash with the laws and regulations below and below them. Constitutional studies are considered very important in the current conditions, especially for Indonesia.Keywords: Environtmental Law; Constitution; Regulation